Evaluating Hierarchical Diversity and Sustainability of Public Transport: From Metropolis to a Weak Transport Demand Area in Western Japan - Nakase, Ryota; Chou, Chun-Chen; Aoki, Yasuchika; Yoh, Kento; Doi, Kenji (Frontiers in Sustainable Cities, 2021)
A variety of transport options must be utilized to enhance public transportation sustainability. Previous studies have rarely developed quantitative methods for evaluating the performance of transport diversity. Thus, this study proposes measurement indicators to evaluate transport diversity on the basis of biodiversity indicators. For the hierarchy of public transport networks, we considered that the public transport system is analogous to ecosystems with a taxonomic hierarchy. The number of operation stations, route length, and operating frequency were used to evaluate the spatial and temporal coverage of the transport services. We analyzed the latent correlation between transport diversity and sustainable transport indicators and then examined the spatial distribution of transport diversity. By visualizing the spatial distribution of transport diversity, we found that high-speed railway stations are instrumental in the hierarchy of public transport networks. Furthermore, improving diversity would increase the modal share of public transport, which is considered crucial for developing sustainable transport, especially in the period of depopulation. Finally, this paper presents a demonstration experiment conducted in a regional city that introduced a variety of transport services integrated on a MaaS platform, attempting to provide a multimodal and seamless mobility service in a weak transport demand area.